Perspectivas atuais sobre a sobrecarga do cuidador em saúde mental - Cardoso, Lucilene (2012)
A systematic literature review was performed regarding the burden on mental health caregivers. The studies were selected from the Virtual Health Library - Biblioteca Virtual de Saúde (BVS), using the keyword caregiver burden. The main criteria for this study were: full-text articles published between 2000 and 2010, in Portuguese, English or Spanish; indexed on the BVS databases; which investigated the burden of mental health caregivers, and had caregivers as the main subject. The analysis was performed considering the following: title, year of publication, objectives, methodological approach, instruments and main results. The analysis of 114 full-text articles showed the predominant objectives were the burden on informal caregivers and the validation of psychometric scales, particularly the Zarit Scale. Some studies showed an association between high levels of burden, feelings of guilt and depressive symptoms. On the other hand, psycho-educational interventions were indicated as having a positive impact. This theme has a growing scientific interest and there is a need for deeper studies addressing formal caregivers.